Envisioning Criminology
XXVI, 271 p. 30 illus., 16 illus. in color.
Keywords: Th is book covers research design and methodology from a unique and engaging point of view, based on accounts from infl uential researchers across the fi eld of Criminology and Criminal Justice. Most books and articles about research in criminology and criminal justice focus on how the research was carried out: the data that were used, the methods that were applied, the results that were achieved. While these are all important, they do not present a complete picture. Envisioning Criminology: Researchers on Research as a Process of Discovery aims to fi ll that gap by providing nuance--the “back story” of why researchers selected particular problems, how they approached those problems, and how their background, training, and experience aff ected the approaches they took. As the contributions in this book demonstrate, research is not a cut-and-dried process, as all too many methods books imply, but a living, breathing–and in some ways quirky– process that is infl uenced by non-“scientifi c” factors. Th e path taken by a researcher is important, and an appreciation of his or her background, experience, knowledge–and the setbacks and triumphs of performing the research–provides a much more complete picture of how research is done. Th e twenty-eight chapters in this book describe the back stories of their authors, which serve to enlighten readers about the interplay between the personal and the methodological. While primarily aimed as a textbook, this work will also be of interest to researchers in Criminology and Criminal Justice, and related Social and Behavioral Science fi elds as an account of how seminal researchers in the fi eld developed their key contributions.